2016
DOI: 10.1063/1.4958517
|View full text |Cite
|
Sign up to set email alerts
|

Stability of 40 phenolic compounds during ultrasound-assisted extractions (UAE)

Abstract: Abstract. Phenolics have been positively associated with many health benefits due to their prominent antioxidant activities. Sample extractions are required before chromatographic measurements for the determination of phenolics in matrices. Hence, the aim of this study was to assess the stability of 40 phenolic compounds of different families (benzoic acids, benzoic aldehydes, cinnamic acids, catechins, stilbenes, and flavonols) under conditions of ultrasound-assisted extraction (UAE). The influence on the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…Overall, the extracts produced by ultrasounds were characterized by lower antioxidant activity in comparison to other techniques. It can be assumed that ultrasounds negatively affect the stability of polyphenolic compounds, therefore the antioxidant potential of these extracts is lower, which was also shown in previous studies [ 27 , 28 ]. In addition, Sun and co-investigators—who were studying the influence of sonification on various parameters of fresh apple juice—noticed a significant decrease of phenolic content and antioxidant activity measured by oxygen radical absorption capacity assay (ORAC).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Overall, the extracts produced by ultrasounds were characterized by lower antioxidant activity in comparison to other techniques. It can be assumed that ultrasounds negatively affect the stability of polyphenolic compounds, therefore the antioxidant potential of these extracts is lower, which was also shown in previous studies [ 27 , 28 ]. In addition, Sun and co-investigators—who were studying the influence of sonification on various parameters of fresh apple juice—noticed a significant decrease of phenolic content and antioxidant activity measured by oxygen radical absorption capacity assay (ORAC).…”
Section: Resultssupporting
confidence: 61%
“…On the other hand, several studies revealed that application of ultrasounds significantly increased concentration of polyphenols and antioxidant activity of the extracts [ 30 , 31 , 32 , 33 , 34 ]. However, according to Setyaningsih et al 2016, an increase in antioxidant potential and phenolics concentration is observed to a temperature of 60–70 °C; above this level, a significant deterioration of polyphenols may be observed, which also decreases antioxidant activity of the samples [ 27 ]. Zapata and co-investigators—who studied the effect of pH, temperature and time of extraction on the antioxidant properties of Vaccinium meridionale —observed that an increase of temperature resulted in more efficient extraction of polyphenols.…”
Section: Resultsmentioning
confidence: 99%
“…Most commonly, total PHT content is quantified by colorimetric methods, generally used for detection of phenolics, like Folin–Ciocalteu, Folin–Denis, and Prussian blue assays. The use of this assay conceals the chemical diversity of individual compounds present but because these compounds are reactive, polar, and structurally related to each other, there is a lack of more sophisticated analysis methods [24,27,30,84].…”
Section: Brown Algae Phenolicsmentioning
confidence: 99%
“…(124.65 mg GAE/g) [28]. In the order Fucales (Table 2) the most investigated species were Ascophyllum nodosum [51,56,58,83], Fucus serratus [48,51,55,69], Fucus vesiculosus [46,47,51,55,84], and Himanthalia elongata [53,54,61,72]. The reported species were also the richest in phenolics: 159 mg PGE/g (51) and 1.4 mg GAE/g dw [83] in Ascophyllum nodosum , 240 mg PGE/g [51] and 81.93 mg GAE/g [57] in Fucus serratus and 277 mg PGE/g [47] and 165 mg GAE/g dw [48].…”
Section: Brown Algae Phenolicsmentioning
confidence: 99%
“…Temperature is an influential factor in the extraction of bioactive compounds that may affect the stability of phenolic compounds [52]. Using higher temperatures was discarded, because it may reduce the recovery, since these compounds are thermally sensitive, and thus can be easily degraded by the hydrolysis of glucoside compounds and form their corresponding unstable aglycones or by the hydrolytic opening of the heterocyclic ring that would form chalcone in the case of anthocyanins [53].…”
Section: Optimal Conditionsmentioning
confidence: 99%